Transformations of the New Germany - Starkman, R.; Starkman, R. (Studies in European Culture and History, 2006)
This collection demonstrates the persistence of the initial anxieties about a united Germany and its rapid absorption of the German Democratic Republic, and also suggests a potential optimism that, despite much contemporary domestic disenchantment, the new Germany continues to thrive as a European democracy endeavouring to confront its past.